ANALISIS PROSES BERPIKIR SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN LANGKAH POLYA DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VIII SMP AL AZHAR SYIFA BUDI TAHUN PELAJARAN 2013/2014 - Supriadi, Danar; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research is aimed to describe: (1) studentâs thinkingÂ process with high emotional quotient in solving mathematics problem based on Polyaâs step, (2) studentâs thinkingÂ process with middle emotional quotient in solving mathematics problem based on Polyaâs steps, and (3) studentâs thinkingÂ process with high emotional quotient in solving mathematics problem based on Polyaâs step. This research was a qualitative research. The subject of this research was taken by using purposive sampling. The subject of this research were nine of 8th grade students at SMP Al Azhar Syifa Budi Solo, consisting of three students with high emotional quotient, three students with middle emotional quotient, and three students with low emotional quotient. The techniques of collecting the data in this research were questionnaire, test, and interview. The techniques of validating the data were time triangulation. The techniques of analyzing the data was Miles and Huberman concept, namely, data reduction, data presentation, and conclusion drawing. This research finally provide the studentâs thinking process as follows.Â Students with high and medium emotional quotient are: (1) able to understand the problem by using a logical thinking process to understand the problem, (2) able to construct a problem solving plan to synthesize the problem, (3) able to carry out the problem solving plan to decide and to draw up the conclusion, and (4) able to re-evaluate the answer and to draw up the conclusion.Â Students with low emotional quotient are: (1) not able to understand the problem well because the canât apply perfectly a thinking process to understand the problem, (2) not able to construct a problem solving plan to synthesize the problem, (3) not able to carry out the problem solving plan well, and (4) not able to re-evaluate the answer and to draw up the conclusion well.Keywords: thinking process, problem solving, emotional quotient